2016
DOI: 10.1017/s1431927616011570
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Second Harmonic Generation Discriminates Between Fresh and Aged Starch-Based Adhesives Used in Cultural Heritage

Abstract: In this work, we report that polarization second harmonic generation (PSHG) microscopy, commonly used in biomedical imaging, can quantitatively discriminate naturally aged from fresh starch-based glues used for conservation or restoration of paintings, works of art on paper, and books. Several samples of fresh and aged (7 years) flour and starch pastes were investigated by use of PSHG. In these types of adhesives, widely used in cultural heritage conservation, second harmonic generation (SHG) contrast originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…These techniques under different modalities provide new insights for the assessment of appropriate conservation methods that have to be applied for various CH objects of high artistic or cultural significance [79,115]. Recent studies have demonstrated the potential of these techniques for depth resolved imaging of materials in cultural heritage, such as varnishes [79], lining glues [80,81], paintings [75], historical coatings [82], and corrosion layers on metal-based artifacts [84]. Fruitful key information concerning the determination of the different layers, precise thickness or surface topography, nature of the different materials, and cracks in the layers has been extracted.…”
Section: Non-linear Microscopymentioning
confidence: 99%
“…These techniques under different modalities provide new insights for the assessment of appropriate conservation methods that have to be applied for various CH objects of high artistic or cultural significance [79,115]. Recent studies have demonstrated the potential of these techniques for depth resolved imaging of materials in cultural heritage, such as varnishes [79], lining glues [80,81], paintings [75], historical coatings [82], and corrosion layers on metal-based artifacts [84]. Fruitful key information concerning the determination of the different layers, precise thickness or surface topography, nature of the different materials, and cracks in the layers has been extracted.…”
Section: Non-linear Microscopymentioning
confidence: 99%
“…Since the 1990s, newly developed commercial low noise, high stability, solid‐state ultrafast pulsed lasers enable high quality laser scanning nonlinear microscopy . The following lasers have been used for SHG microscopy of starch: Ti:Sapphire at 800–854 nm , Yb:KGW at around 1030 nm , Yb fiber laser at 1040 nm , Nd:YAG at 1064 nm , and a Cr:Forsterite at 1230 nm , providing a pulse energy of at least several nJ. Laser wavelengths ranging from 800 to 1230 nm result in SHG signal wavelength falling within the high sensitivity range of PMT detectors (400–650 nm).…”
Section: Second Harmonic Generation Microscopymentioning
confidence: 99%
“…Single photon counting detection is suitable for low photon count applications as needed for imaging very small or highly altered starch granules that emit low intensity SHG signal . The SHG signal intensity is quite high in wild‐type (wt) starches and, therefore, analog detection, (common in commercial microscopes) often is also suited for starch imaging . Another feature of the specialized microscope presented in Fig.…”
Section: Second Harmonic Generation Microscopymentioning
confidence: 99%
See 2 more Smart Citations